2020
DOI: 10.3390/ani10101886
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of on/at Line Methods to Determine Boar Taint and Boar Taint Compounds: An Overview

Abstract: Classification of carcasses at the slaughter line allows an optimisation of its processing and differentiated payment to producers. Boar taint is a quality characteristic that is evaluated in some slaughter plants. This odour and flavour is mostly present in entire males and perceived generally by sensitive consumers as unpleasant. In the present work, the methodologies currently used in slaughter plants for boar taint classification (colorimetric method and sensory quality control-human nose) and the methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…Compared to androstenone, the majority of consumers are able to perceive skatole in pork, and dislike it [ 8 ]. Currently, a number of techniques for identification of carcasses with boar taint in commercial abattoirs exist, with their own cost-implications [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to androstenone, the majority of consumers are able to perceive skatole in pork, and dislike it [ 8 ]. Currently, a number of techniques for identification of carcasses with boar taint in commercial abattoirs exist, with their own cost-implications [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous analytical methods used to evaluate these compounds; a review of those methods can be found in Haugen et al (2012), where the authors highlight the need for a standardization of methods to quantify boar taint compounds. Additionally, new methods that can be used on the slaughter lines were reviewed by Font-i-Furnols et al (2020).…”
Section: Methods For Measuring Boar Taintmentioning
confidence: 99%
“…This could lead to different results for the same sample. This stresses the importance of standardizing sensory evaluation protocols, from the training of the assessors to the evaluation per se performed in the slaughterhouse [27,57,58].…”
Section: Understanding the Differences Between The Voc Profiles Generatedmentioning
confidence: 99%